Forum Młodych Chirurgów Patients with coronary artery disease disqualified for myocardial revascularization. Proceeding, the way of treatment and chance for better prognosis in the period of intensive development of cardiology and cardiac surgery - Kozłowska, Mariola; Hudzik, Bartosz; Hawranek, Michał; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
The review presents the experience of different authors and results of their research in those patients with coronary artery disease who are disqualified for direct revascularization of a specified area of the myocardium. Patients are qualified for a different kind of treatment using proper prognostic scales which estimate the operation risk. Nowadays with the intensive development of cardiology we have lots of therapeutic methods for those patients from medical treatment to using more complicated techniques like transmyocardial laser revascularization, application growth factors, gene therapy, angiogenic proteins, and steam and progenitor cells, which are still being investigated.